ANALISIS ANOMALI PERDAGANGAN SAHAM TERHADAP RETURN SAHAM IDX30 DI BURSA EFEK INDONESIA - Ahmad Pauzi, (2022)
The aim of this research is to discover (1) regardless of whether there is a distinction in daily stock return during stock trading, (2) whether there is a Monday Effect in stock trading, (3) whether there is a Weekend Effect in stock trading. The sample of this research where 27 companies that are members for the period January 2020 to December 2020 which were chosen utilizing the purposive sampling method. The technique used to analyze the hypothesis is the Kruskal Wallis and the Wilcoxon Sign Rank Test with the help of Microsoft Excel 2019 and SPSS 25 programs. The results provide evidence that (1) daily stock returns have differences during the stock trading period at IDX30, (2) The Monday Effect occurs on stock trading on IDX30, and (3) The Weekend Effect occurs on stock trading on IDX30.